EVALUASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PERKOTAAN DI KOTA BANDAR LAMPUNG - Noverman Duadji (Indonesian Journal of Dialectics, 2012)
This research started from a research problem that stated into a question statement 'how is the evaluation program of PNPM MP in Bandar Lampung?'. According to the problem and reason, the research used qualitative method. The research explained that the program document from central government regulate and state the poor as target group of the program, but the substance of the program on the city level can not touch the poor needs and problems; or in other word the program is off target. The formal problem, the program and the program organization implementer is not appropriate to the poor substantive problem in this city. According to the statement above, the PNPM MP program in Bandar Lampung is not feasible. It caused by: (1) the viability of data and data base management are less; (2) the problem identification doesn't use the holistic analysis, yet. The problem and the target group are specified by the principle of the even distribution of fund and program to each sub district and sub district administrative area; (3) the retardation of the survey. TKPKD and TKMPKD Lampung Province had the time limit employed the survey; (4) the program produced by the questionnaires which the program narrowly interpreted the substance of program from the central government document, especially the physical infrastructure which is not interlinked to the poor economic activity and empowerment. According to the impact point analysis, the program contributed 1.6% if the program implemented successfully; (5) the anticipative action, modification and program monitoring just addressed to: (a) administrative andmanagement program and (b) the physical progress and the fund absorption; (6) as program implementer organization, LKM and KSM are elitist (elite representation) and top down process and mechanism about its formation; and (7) depend on the role of donor agency (World Bank and Islamic Development Bank) and the role of central government. Bandar Lampung governmental has no a free hand to create the program accord with the local specific of the poor in its area. Based on description above, this research strengthens the Rossi's theory. The formation of a new concept stated a proposition 'the successfully program evaluation depend on program formation and implementer organization'.